POTENSI NIKEL LATERIT PADA PROSPEK PUU NUNU, KECAMATAN KABAENA SELATAN, KABUPATEN BOMBANA, PROVINSI SULAWESI TENGGARA - Qoyyibi, Dava Saliham; Sugarbo, Oky; Hartono, Hill Gendoet (KURVATEK, 2026)
Nickel occurrences in Indonesia are generally found as lateritic nickel deposits derived from the residual weathering of bedrock from ophiolite or ultramafic complexes. Sulawesi Island and the surrounding smaller islands possess significant nickel potential due to their complex geological setting. Therefore, a geological study is necessary to assess this potential by conducting surface mapping. The study area is located in Southeast Sulawesi and falls within the mining business license (IUP) area of PT. Tambang Bumi Sulawesi. This research aims to carry out surface geological mapping, with the objective of identifying geological conditions, including geomorphology, stratigraphy, geological structures, and resource estimation in areas with lateritic nickel potential. The results of the study indicate that the geomorphological units consist of strongly undulating-denudational hills and weakly to strongly undulating-denudational areas. The stratigraphy of the study area, from oldest to youngest, comprises lherzolite and hornblende pyroxenite of the Ultramafic Complex, which are unconformably overlain by mica schist and marble of the Pompangeo Complex. The geological structure is characterized by a sinistral (left-lateral) left slip fault trending northwest-southeast. Resource estimation using the ordinary kriging method yielded a total measured resource volume of 518,855 m³, with an estimated tonnage of 778,283 tons in the lateritic potential area.